Effect of molecular weight and chemical structure on thermal and rheological properties of gelling κ/ι-hybrid carrageenan solutions - Hiléia K. S. Souza (2011)
Three κ/ι-hybrid carrageenan polysaccharides with distinct molecular mass and content of -carrageenan disaccharide units were isolated from Mastocarpus stellatus seaweeds. The viscoelastic and thermal properties of 2 wt% κ/ι-hybrid carrageenan solutions with ionic strength tuned by the addition of NaCl salt were studied by means of rheological tests and differential scanning calorimetry (DSC). All solutions form a gel upon cooling. The gel elasticity decreases with the content in ι-carrageenan disaccharide units, and does not correspond to the additive elasticity of a - and a ι-carrageenan networks. The highest gel elasticity is obtained with the lowest molecular mass. In 0.1M NaCl, two gelling processes are evidenced. The first increase in solution viscosity upon cooling coincides with a thermal transition process, which is assigned to a coil-to-helix conformational transition. The transition depends on both molecular mass distribution and chemical structure. The same dependencies are observed for the gel melting behaviour as all rheological and thermal processes determined are shifted to higher temperature with decreased molecular mass or increased content in ι-carrageenan disaccharide units.